Strategi Peningkatan Pendapatan Masyarakat Melalui Pemanfaatan Kredit Mikro dan Ultra Mikro Berbasis Kearifan Lokal Gunung Padang - Jan Prince Permata; Hardy R Hermawan; Azka Aurelia Dewanti; Ngyuyen Kim Thanh; Deden Prayitno; Fanky Antoneus Sorongan; Markonah Markonah; Rahmawati Mohd Yusoff (Jurnal Serambi Abdimas, 2026)
This International Community Engagement Program (PKM) aims to enhance the income of local communities surrounding the Gunung Padang heritage site through a synergy of micro/ultra-micro (UMi) credit, local wisdom (adat, mutual cooperation, deliberation), and digital payment systems. Conducted on 18 September 2025, the program involved 55 participants, including five Perbanas doctoral students, eight international students, five lecturers, ten cultural practitioners, ten micro and ultra-micro entrepreneurs, ten Tourism Awareness Group (Pokdarwis) members, and representatives from the Karya Mukti Village and Cianjur Regency Governments. The activities consisted of lectures, discussions, field problem identification covering credit access, digital payment literacy, business training needs, and financial management and a site visit to Gunung Padang. Recommendations generated include adaptive UMi product design, strengthening of group lending and social capital, QRIS registration assistance, digital payment training, development of community-based tourism (CBT) packages rooted in local wisdom, and a simple Social Return on Investment (SROI) framework to monitor economic impacts. The article integrates insights from microfinance, social capital, CBT, the Business Model Canvas, and SROI to propose measurable and practical strategies.